Adverse events of extracorporeal ultrasound-guided high intensity focused ultrasound therapy. - Tinghe Yu (Public Library of Science (PLoS), 2011)
Background High-intensity focused ultrasound (HIFU) is considered to be an alternative to surgery. Extracorporeal ultrasound-guided HIFU (USgFU) has been clinically used to treat solid tumors. Preliminary trials in a small sample of a Western population suggested that this modality was safe. Most trials are performed in China thereby providing comprehensive data for understanding the safety profile. The aim of this study was to evaluate adverse events of USgFU therapy. Methods and findings Clinical data were searched in 2 Chinese databases. Adverse events of USgFU were summarized and compared with those of magnetic resonance-guided HIFU (MRgFU; for uterine, bone or breast tumor) and transrectal ultrasound-guided HIFU (for prostate cancer or benign prostate hyperplasia). USgFU treatment was performed using 7 types of device. Side effects were evaluated in 13262 cases. There were fewer adverse events in benign lesions than in malignant lesions (11.81% vs. 21.65%, p<0.0001). Rates of adverse events greatly varied between the disease types (0-280%, p<0.0001) and between the applied HIFU devices in both malignant (10.58-44.38%, p<0.0001) and benign lesions (1.67-17.57%, p<0.0001). Chronological analysis did not demonstrate a decrease in the rate of adverse events. Based upon evaluable adverse events, incidences in USgFU were consistent with those in MRgFU or transrectal HIFU. Some side effects frequently occurred following transrectal HIFU were not reported in USgFU. Several events including intrahepatic metastasis, intraoperative high fever, and occlusions of the superior mesenteric artery should be of particular concern because they have not been previously noted. The types of adverse events suggested that they were ultrasonic lesions. Conclusion The frequency of adverse events depended on the location of the lesion and the type of HIFU device; however, side effects of USgFU were not yet understood. USgFU did not decrease the incidence of adverse events compared with MRgFU.